2005
DOI: 10.1016/s1808-8694(15)31314-8
|View full text |Cite
|
Sign up to set email alerts
|

Apocrine carcinoma in the parotid gland and in the submandibular region

Abstract: The objectives of this paper are to report a case of apocrine carcinoma and the discussion of aspects related to its diagnosis, treatment, and prognosis. Carcinomas with apocrine differentiation not related to extramammary Paget's disease, ductal breast carcinoma, Moll's glands adenocarcinoma and ceruminous glands carcinoma are very uncommon tumors. We report a case of a 51-year-old black woman who developed apocrine carcinoma lesions in the head and neck region. Two lesions involved her left parotid gland (fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The prognosis for cutaneous apocrine carcinoma is variable. There have been reports of local recurrences and regional lymph node metastasis occurring years after initial excision 10 …”
mentioning
confidence: 99%
“…The prognosis for cutaneous apocrine carcinoma is variable. There have been reports of local recurrences and regional lymph node metastasis occurring years after initial excision 10 …”
mentioning
confidence: 99%
“…17 The therapeutic effect of chemotherapy on SGC has not been confirmed, only a few successful have been reported in single case reports. 18 According to previous literatures, the 5-year survival rate for SGC is less than 30%; the local recurrence rate is as high as 50%; and 60% of the patient exhibit metastasis within 2 years after surgery. 19,20 In the study of head and neck sweat gland adenocarcinoma (SGA), Unsal et al reported that the overall prognosis is relatively good: 5-, 10-, and 20-year diseasespecific survival at 94.6%, 89.6%, and 79.8%, respectively.…”
Section: Discussionmentioning
confidence: 95%
“…17 The therapeutic effect of chemotherapy on SGC has not been confirmed, only a few successful have been reported in single case reports. 18…”
Section: Discussionmentioning
confidence: 99%